2016
DOI: 10.1111/1744-7917.12322
|View full text |Cite
|
Sign up to set email alerts
|

Obligatory parthenogenesis and TE load: Bacillus stick insects and the R2 non‐LTR retrotransposon

Abstract: Transposable elements (TEs) are selfish genetic elements whose self-replication is contrasted by the host genome. In this context, host reproductive strategies are predicted to impact on both TEs load and activity. The presence and insertion distribution of the non-LTR retrotransposon R2 was here studied in populations of the strictly bisexual Bacillus grandii maretimi and of the obligatory parthenogenetic Bacillus atticus atticus. Furthermore, data were also obtained from the offspring of selected B. a. attic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…The present analysis, carried out with the same method described in Bast et al (, i.e., read mapping as a proxy for TE content), indicated that the TE content of the putatively parthenogenetic L. apus lubbocki is significantly lower than that of L. arcticus . These preliminary results, therefore, are in line with the hypothesis that TE lineages with lower proliferating activity were selected in parthenogenetic organisms to favour the survival of both host organisms and TE lineages (Bonandin et al, ; Bull, Molineux, & Rice, ; Wright & Finnegan, ). However, it could be interesting to evaluate TE content variation at the population level, considering polymorphic insertions and the relative frequency of these insertions within populations/taxa.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The present analysis, carried out with the same method described in Bast et al (, i.e., read mapping as a proxy for TE content), indicated that the TE content of the putatively parthenogenetic L. apus lubbocki is significantly lower than that of L. arcticus . These preliminary results, therefore, are in line with the hypothesis that TE lineages with lower proliferating activity were selected in parthenogenetic organisms to favour the survival of both host organisms and TE lineages (Bonandin et al, ; Bull, Molineux, & Rice, ; Wright & Finnegan, ). However, it could be interesting to evaluate TE content variation at the population level, considering polymorphic insertions and the relative frequency of these insertions within populations/taxa.…”
Section: Discussionsupporting
confidence: 85%
“…However, empirical studies on bisexual and parthenogenetic lineages have given contrasting results. Studies on Bacillus stick insects have indicated that some parthenogenetic lineages have a relatively high TE load (Bonandin, Scavariello, Luchetti, & Mantovani, ; Bonandin, Scavariello, Mingazzini, Luchetti, & Mantovani, ), while analyses have shown less insertions in obligately parthenogenetic Daphnia lineages than in cyclically parthenogenetic Daphnia lineages (Valizadeh & Crease, ). Recent genomewide studies have highlighted similar TE contents in bisexual and parthenogenetic taxa, including D. pulex lineages (Bast et al, ; Kraaijeveld et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, transfection of LINE‐1 into cells induces production of IFNβ . Also, a recent study showed that blood mononuclear cells from ~17% of SLE patients have detectable cyclic GMP‐AMP, the second messenger exclusively made by cGAS when it is activated by aberrant intracellular DNA . Given the minute quantities and rapid turnover of this second messenger, these data likely represent an underestimate.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest a link between the variability for number and location of colocalized NOR/telomeric sequences and the presence of R2 retrotransposons. R2 retrotransposons, presenting a strict sequence specificity for an insertion target-site in the 28S rDNA, have been reported in bisexual and parthenogenetic populations of B. rossius, with a very high copy-number (Martoni et al 2015;Satovic et al 2016;Bonandin et al 2017;. Moreover, increased chromosome breakages and rearrangements have been observed in all taxa embodying the B. rossius genome, particularly in the parthenogenetic hybrids ( Figure 5(b,c,d)).…”
Section: Variability Of Ribosomal Sequences and Chromosome Rearrangemmentioning
confidence: 83%